2x + y = -2
5x + 3y = -8
We can isolate y in the first equation and substitute its expression for y into the second equation to find x:
2x + y = -2
y = -2x - 2
----
5x + 3y = -8
5x + 3(-2x - 2) = -8
5x - 6x - 6 = -8
- x - 6 = -8
-x = -2
x = 2
Now we can substitute that into y = -2x - 2 to find y:
y = -2(2) - 2
y = -4 - 2
y = -6
Finally, we must check our work by plugging both values back into both original equations:
2(2) + (-6) = -2 --> 4 - 6 = -2 <--True
5(2) + 3(-6) = -8 --> 10 - 18 = -8 <--True
Answer:
x = 2
y = -6
Hope this helps.